A Multi-layer Security Scheme (MLSS) for Digital Images Contents - Faraj Ali Faraj Alyaqobi, Nor Adnan Yahaya (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Digital images and their contents are increasingly being utilized in numerous applications, especially in the context of the Internet of Things (IoT). The rapid growth of IoT has facilitated the sharing and transmission of vast amounts of data in today's modern world. Consequently, various applications relying on images are now generating a substantial volume of data that requires extensive processing, including the manipulation of images and associated digital elements. Protecting sensitive information within these digital images is of utmost importance, particularly for applications that store critical data. The exposure of such data to the public would pose significant risks to numerous applications and systems. However, despite the advantages offered by IoT, devices and resources connected to this network still face substantial security challenges. In this research, we propose a multi-layer security scheme (MLSS) that employs a diverse range of security procedures applicable to various forms of information, including images. The MLSS consists of three key processes, aimed at preserving information integrity, confidentiality, and accessibility. An evaluation of this scheme has demonstrated its effectiveness, safety, and with a very low range of data loss.